The Influence of Digital Accounting, Digital Payment, and Financial Management on Improving the Financial Performance of Micro, Small, and Medium Enterprises in the Digital Era (Study on MSMEs in Bandar Lampung) - Nina Al Azizah; Nurlaili; Arifa Kurniawan (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the influence of digital accounting, digital payment, and financial management on improving the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Bandar Lampung City in the digital era. The study population was all MSMEs registered with the Bandar Lampung City Cooperatives and MSMEs Office. A sample of 120 MSMEs was determined using a purposive sampling technique. The analysis method used was multiple linear regression with the help of SPSS version 26. The results showed that digital accounting had a positive and significant effect on MSME financial performance, digital payment had a positive and significant effect on financial performance, and financial management also had a positive and significant effect. Simultaneously, the three independent variables significantly influenced MSME financial performance with a contribution of 68.4%. This study implies that the adoption of digital technology and good financial management practices are key to improving MSME financial performance in the digital era.